The Role and Significance of Existing Educational Programs and Technologies in Developing Managerial Competence - Feruza Jalolova Mirkamol qizi (Scientific Trends, 2025)
This article analyzes the role and significance of current educational programs and modern learning technologies in the development of managerial competence. The formation of managerial skills and the enhancement of professional qualities through innovative approaches are considered among the key priorities of today’s education system. The article examines the structure and content of educational programs, their contribution to professional competence development, and the impact of digital education technologies, interactive methods, and continuous professional growth on managerial capacity. Based on the analysis of best practices, recommendations are provided to improve the implementation of educational processes aimed at fostering managerial competence.
Keywords: managerial competence, educational program, educational technology, innovative approach, professional development, managerial skills, digital education, interactive methods, quality control, learning effectiveness.